?Historical Excellence? in Football World Cup Tournaments: Empirical Evidence with Data From 1930 to 2002 - Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Most of the football papers that measure the international performances focus on the ranking system provided by the FIFA. Surprisingly, the World Cup per se has not been analyzed intensively. This paper as a novelty reports empirical evidence of international team performances in the World Cup tournaments between 1930 and 2002. The paper investigates to which extent economic, demographic, cultural and climatic factors have an impact on national teams' performances. Strong evidence is reported that nations with a stronger football tradition perform better.
Keywords: L83; 330; football; soccer; FIFA; culture